REVERSE MARKETING AND ITS EFFECT ON SUSTAINABLE DEVELOPMENT - Dr. Rabie yaseen saud , Dr.Zaid yaseen saud, Marwan sabah hasan, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to identify reverse marketing as a major variable and its impact on achieving sustainable development. The research was applied to a sample of employees of the Ministry of Water Resources, As the topic of reverse marketing has been of great importance to its novelty and its repercussions on the reality of these department at the present and future time. The research is based on the dimensions of the independent variable of reverse marketing (price, service, promotion) and the dimensions of the dependent variable, sustainable development (economic, environmental, and social). The research consisted of four sections, the first of which dealt with the research methodology, The second talked about the theoretical framework, As for the third, it contained the practical aspect, And the fourth touched on the most important conclusions and recommendations that were reached. A questionnaire was designed to collect data and distributed to a sample of (55) employees, where the answers were analyzed under the statistical program spss. The research has reached the most important conclusions that came out, and the most important of them are: There is an active and essential role of reverse marketing in achieving sustainable development, in addition reverse marketing seeks to regulate the consumption of harmful products, direct the consumer, raise awareness and limit the use of such products. On the results of the conclusions, a number of recommendations were made, the most important of which were: It recommends adopting reverse marketing in organizations and agencies, conducting more research studies and increasing interest in reverse